2010
DOI: 10.1523/jneurosci.4997-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of α9-Containing Cholinergic Nicotinic Receptors in the Rat Adrenal Medulla: Implication in Stress-Induced Functional Plasticity

Abstract: An increase in circulating adrenal catecholamine levels constitutes one of the mechanisms whereby organisms cope with stress. Accordingly, stimulus-secretion coupling within the stressed adrenal medullary tissue undergoes persistent remodeling. In particular, cholinergic synaptic neurotransmission between splanchnic nerve terminals and chromaffin cells is upregulated in stressed rats. Since synaptic transmission is mainly supported by activation of postsynaptic neuronal acetylcholine nicotinic receptors (nAChR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 65 publications
4
65
0
1
Order By: Relevance
“…In line with previous studies, our results have shown that inescapable stress causes widespread alterations in animal performance, including reduced body weight loss, brain weight, food intake, increased anorexia and water intake and adrenal gland weight (McEwen, 2007;Colomer et al, 2010;G Hunter, 2012;Guérineau et al, 2012;Lutfy et al, 2012). It would be renowned that according to preceding studies, stress stimulates HPA axis and upsurges secretion of epinephrine and glucocorticoids from the central and cortical parts of the adrenal gland, respectively (McEwen, 2007; B Hunter et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous studies, our results have shown that inescapable stress causes widespread alterations in animal performance, including reduced body weight loss, brain weight, food intake, increased anorexia and water intake and adrenal gland weight (McEwen, 2007;Colomer et al, 2010;G Hunter, 2012;Guérineau et al, 2012;Lutfy et al, 2012). It would be renowned that according to preceding studies, stress stimulates HPA axis and upsurges secretion of epinephrine and glucocorticoids from the central and cortical parts of the adrenal gland, respectively (McEwen, 2007; B Hunter et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…It would be renowned that according to preceding studies, stress stimulates HPA axis and upsurges secretion of epinephrine and glucocorticoids from the central and cortical parts of the adrenal gland, respectively (McEwen, 2007; B Hunter et al, 2010). It has been reported that the reduced level of dopamine in the nucleus accumbens recovers the animal's ability to acquire used to stress following inescapable stress (Dubrovsky, 2005;Viveros et al, 2007;Colomer and Olivos-Oré et al, 2010;Hunter and Bloss et al, 2010). Various parts of reward system are involved in the variation of stress responses and the nucleus accumbens as a main parts of this reward system, acting a vital role in inhibiting the effects of stress (Zhao et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the auditory system, transcripts and/or protein for a9 and a10 subunits have been found in lymphocytes, skin keratinocytes, sperm, dorsal root ganglion, sympathetic neurons, macrophages, and adrenal chromaffin cells (Nguyen et al, 2000;Lustig et al, 2001;Lips et al, 2002;Haberberger et al, 2004;Kurzen et al, 2004;Peng et al, 2004;Kumar and Meizel, 2005;Colomer et al, 2010;Simard et al, 2013). The physiologic role of a9a10 nAChRs in the auditory system has been determined through studies done with a9 and a10 knockout mice (Vetter et al, 1999(Vetter et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, α9α10 nAChRs have been found in adrenal chromaffin cells, where they may modulate responses to stress (7). In addition, transcripts for the α9 and/or α10 subunit have been reported in a variety of nonneuronal cells, including immune cells.…”
mentioning
confidence: 99%